Radiation-induced cerebral contrast enhancements strongly share ischemic stroke risk factors - Eichkorn, Tanja; Lischalk, Jonathan W; Schwarz, Robert; Bauer, Lena; Deng, Maximilian; Regnery, Sebastian; Jungk, Christine; Hörner-Rieber, Juliane; Herfarth, Klaus; König, Laila; Debus, Jürgen (International journal of radiation oncology, biology, physics, 2024)
Purpose: Radiation-induced cerebral contrast enhancements (RICE) are frequent after photon and particularly proton radiation therapy and are associated with a significant risk for neurologic morbidity. Nevertheless, risk factors are poorly understood. A more robust understanding of RICE risk factors is crucial to improve management and offer adaptive therapy at the outset and during follow-up. Methods and Materials: We analyzed the comorbidities in detail of 190 consecutive adult patients treated at a single European national comprehensive cancer center with proton radiation therapy (54 Gy relative biological effectiveness) for LGG from 2010 to 2020 who were followed with serial clinical examinations and magnetic resonance imaging for a median 5.6 years. Results: Classical vascular risk factors including age (>= 50 vs <50 years: 1.6-fold; P = .0024), hypertension (2.7-fold; P = .00012), and diabetes (11.7-fold; P = .0066) were observed more frequently in the cohort that developed RICE. Dyslipidemia (2.1-fold), being overweight (2.0-fold), and smoking (2.6-fold), as well as history of previous stroke (1.7-fold), were also more frequently observed in the RICE cohort, although these factors did not reach the threshold for significance. Multivariable regression modeling supported the influence of age (P = .05), arterial hypertension (P = .01), and potentially male sex (P = .02), diabetes (P = .0008), and smoking (P = .001) on RICE occurrence over time, independent of each other and further vascular risk factors. If RICE occurred, bevacizumab treatment was 2-fold more frequently needed in the cohort with vascular risk factors, but RICE long-term prognosis did not differ between the RICE subcohorts with and without vascular risk factors. Conclusions: This is the first report in the literature demonstrating that RICE strongly shares vascular risk factors with ischemic stroke, which further enhances the nebulous understanding of the multifactorial pathophysiology of RICE. Classical vascular risk factors, especially age, hypertension, and diabetes, clearly correlated independently with RICE risk. Risk-adapted screening and management for RICE can be directly derived from these data to assist in clinical management. (c) 2024 The Author(s). Published by Elsevier Inc. This is an open access article under the CC BY -NC -ND license (http://creativecommons.org/licenses/ by-nc-nd/4.0/)
Gesehen am 10.09.2024